Clinicopathological importance of immunohistochemical expression of OCT4, c-MYC and Ki-67 in colorectal cancer - Rabia Hursitoglu; Abdulkadir Yasir Bahar; Sezen Koçarslan; Gökmen Aktaş; Neslihan Kurtul; Emine Kılınç (Polish Journal of Pathology, 2024)
Cancer stem cells (CSCs) are cancer cells responsible for cancer initiation, growth, metastasis, recurrence and resistance to treatment. OCT4 and c-MYC are widely accepted as CSC markers. In this study, we examined the immunohistochemical co-expression of c-MYC and OCT4 with Ki-67 in colorectal cancers (CRC) and the relationship between the results and prognostic and therapeutic data. c-MYC, OCT4 and Ki67 immunohistochemical staining was applied to 162 colectomy cases. Nuclear staining was considered for immunohistochemical staining. Survival in the c-MYC H /OCT4 H subtype, which is one of the subtypes based on c-MYC and OCT4 co-expression, was different from the other subtypes and statistically significant. Although these markers are enriched in cancer stem cells, their specificity in identifying them is limited. CSCs become dormant in the cell cycle, which is one of the mechanisms of escape in drug resistance. We hypothesized that including Ki67 immunohistochemical staining in our study would increase the specificity in detecting CSCs. Our results show that the Ki67 L /c-MYC H /OCT4 H subgroup was associated with lower survival and resistance to treatment compared to the other subgroups. This finding may provide insight into cases with a high number of CSCs and guide targeted treatments.